Orthogeriatrics and Hip Fracture Care in the UK: Factors Driving Change to More Integrated Models of Care - Middleton, Mark (Geriatrics (Basel), 2018)
In the United Kingdom (UK), approximately 80,000 hip fractures each year result in an estimated annual cost of two billion pounds in direct healthcare costs alone. Various models of care exist for collaboration between orthopaedic surgeons and geriatricians in response to the complex medical, rehabilitation, and social needs of this patient group. Mounting evidence suggests that more integrated models of orthogeriatric care result in superior quality of care indicators and clinical outcomes. Clinical governance through national guidelines, audit through the National Hip Fracture Database (NHFD), and financial incentives through the Best Practice Tariff (providing a £1335 bonus for each patient) have driven hip fracture care in the UK forward. The demanded improvement in quality indicators has increased the popularity of collaborative care models and particularly integrated orthogeriatric services. A significant fall in 30-day mortality has resulted nationally. Ongoing data collection by the NHFD will lead to greater understanding of the impact of all elements of hip fracture care including models of orthogeriatrics.